Health-related quality of life in former National Collegiate Athletic Association Division I collegiate athletes compared with noncollegiate athletes: A 5-year follow-up - Simon, J. E.; Lorence, M.; Docherty, C. L. (Journal of Athletic Training, 2021)
Context: The effect of athletic participation on lifelong health among elite athletes has received increasing attention, as sport-related injuries can have a substantial influence on long-term health. Objective: To determine the current health-related quality of life (HRQoL) of former National Collegiate Athletic Association Division I athletes compared with noncollegiate athletes 5 years after an initial assessment. Design: Cohort study. Setting: Online survey. Patients or Other Participants: From the former Division I athletes, 193 responses were received (response rate = 83.2%; 128 men, 65 women; age = 58.47 ± 6.17 years), and from the noncollegiate athletes, 169 surveys were returned (response rate = 75.1%; 80 men, 89 women; age = 58.44 ± 7.28 years). Main Outcome Measure(s): The independent variables were time (baseline, 5 years later) and group (former Division I athlete, noncollegiate athlete). Participants completed 7 Patient-Reported Outcomes Measurement Information System scales: sleep disturbance, anxiety, depression, fatigue, pain interference, physical function, and satisfaction with participation in social roles. Results: Sleep disturbance, depression, fatigue, pain, and physical function were significant for time × group interactions (P values < .05), with the largest differences seen in pain and physical function between groups at time point 2 (22.19 and 13.99 points, respectively). Former Division I athletes had worse scores for depression, fatigue, pain, and physical function at follow-up (P values < .05), with the largest differences seen on the depression, fatigue, and physical function scales (8.33, 6.23, and 6.61 points, respectively). Conclusions: Because of the competitive nature of sport, the long-term risks of diminished HRQoL need to become a priority for health care providers and athletes during their athletic careers. Additionally, physical activity transition programs need to be explored to help senior student-athletes transition from highly structured and competitive collegiate athletics to lifestyle physical activity, as it appears that individuals in the noncollegiate athlete cohort engaged in more physical activity, weighed less, and had increased HRQoL.